Outlines of a Pneumatology in the French School of Spirituality 17th Century (Teología, 2018)
Contemporary and confidant of Francisco de Sales, Pedro de Bérulle was born in France in 1575. His work is located in the first half of the 17th century. Being, rather, a spiritual author, his writings have not ceased to manifest a theological density. Among his books stands Grandeurs de Jésus (1623), considered his masterpiece, with a text that combines dogmatic approaches and mystical aspects. The present article tries to expose the pneumatology found in this work where, in general, a clear theology of the incarnation is presented. This theology is inserted in a Trinitarian framework, with a very focused attention on the relationship of the first two Persons. The person and role of the Holy Spirit is not present, but with a conception that allows us to glimpse the limits of the Berullian thought, typical of the theology of the time. The author approaches a balance from the perspective of contemporary theology that helps to better perceive the strengths and weaknesses of the pneumatology of the main reference of the French School of spirituality.
Keywords: France; 17th Century; Trinity; Pneumatology; Current Reading